Musculoskeletal disorder - Jamaludin, Thandar Soe Sumaiyah (IIUM Press, International Islamic University Malaysia, 2018)
The prevalence of the nursing students who is suffering musculoskeletal disorder worldwide is increasing dramatically. For example, in Australia, it is stated that 80% of them experienced it at some body site. On the other hand, musculoskeletal complaints had become significant issues affecting fireman safety and cause injury to them. Several factors had been identified contributing to these problems.